Microstructural changes of Y-doped V-4Cr-4Ti alloys after ion and neutron irradiation. (December 2016) - Watanabe, H.; Yamasaki, K.; Higashijima, A.; Taguma, H.; Nagasaka, T.; Muroga, T.
Highlights: Heavy-ion and fission-neutron irradiation on Y doped V-4Cr-4Ti alloys was carried out at temperatures 673–873 K. During the ion irradiation at 873 K, the microstructure was controlled by the formation of Ti(C, O, N) precipitates lying on the (100) plane. After neutron irradiation at 873 K, fine titanium oxides were also observed in all V alloys. The detailed analysis of EDS showed that the center of the Ti(C, O, N) precipitates was mainly enriched by nitrogen. The results showed that the contribution of not only oxygen atoms picked up from the irradiation environment but also nitrogen atoms is essential to understand the microstructural evolution of V-4Cr-4Ti-Y alloys. Abstract: High-purity Y-doped V-4Cr-4Ti alloys (0.1–0.2 wt. % Y), manufactured by the National Institute for Fusion Science (NIFS), were used for this study. Heavy-ion and fission-neutron irradiation was carried out at temperatures 673–873 K. During the ion irradiation at 873 K, the microstructure was controlled by the formation of Ti(C, O, N) precipitates lying on the (100) plane. Y addition effectively suppressed the growth of Ti(C, O, N) precipitates, especially at lower dose irradiation to up to 4 dpa. However, at higher dose levels (12.0 dpa), the number density was almost at the same levels irrespective of the presence of Y. After neutron irradiation at 873 K, fine titanium oxides were also observed in all V alloys. However, smaller oxide sizes were observed in the Y-doped samples under the same irradiation conditions. The detailed analysis of EDS showed that the center of the Ti(C, O, N) precipitates was mainly enriched by nitrogen. The results showed that the contribution of not only oxygen atoms picked up from the irradiation environment but also nitrogen atoms is essential to understand the microstructural evolution of V-4Cr-4Ti-Y alloys.